Rapid, one-pot procedure to synthesise 103Pd:Pd@Au nanoparticles en route for radiosensitisation and radiotherapeutic applications. Issue 10 (14th March 2015) - Djoumessi, D.; Laprise-Pelletier, M.; Chevallier, P.; Lagueux, J.; Côté, M. F.; Fortin, M.-A.
<x xml:space="preserve">Abstract</x> Radioactive gold–palladium nanoparticles for radiotherapy.